Conservation Agriculture in South Asia - Saharawat, Yashpal Singh; Gill, Mushtaq; Gathala, Mahesh Kumar; Karki, Tika Bahadur; Wijeratne, D.B.T.; Samiullah, Sayed (Burleigh Dodds Science Publishing Limited, 2022)
South Asia, a home of 1.7 billion people houses the most poor and malnourished people globally. The region need to double its food production by 2050. Current scenario puts South Asian agriculture in a dilema facing triple challenges: to increase production to meet the food demand of growing human population with a lower environmental footprint, preserve natural resources and mitigate or adapt to the changing climatic scenarios. Conservation Agriculture offers a number of benefits such as arresting and reversing the resource degradation, decreasing cultivation costs, making agriculture more resource – use-efficient, competitive and sustainable whilst increasing resilience to climatic variability and improving livelihood incomes in South Asia. The CA approach for managing agro-ecosystems is of paramount significance in improving soil health, sustained productivity and maintaining natural biodiversity. However, there is still a large knowledge gap in understanding of nutrient and water management in CA systems.